Efficacy and Safety of Curcuma Longa Extract in Patients with Osteoarthritis: A Literature Review - Halim, Kurnia; Gaol, Christine Lumban; Vira, Patricya; Utomo, Winno Pradana; Mahendika, Devin (Indonesian Journal of Global Health Research, 2024)
Osteoarthritis (OA) is a chronic degenerative inflammatory disease that attacks the joints, especially the knee joints, in millions of people throughout the world. The main symptom of this disease is joint pain. Many studies have shown that components of Curcuma longa have beneficial effects in the pain management of OA patients. Objective to determine the efficacy and side effects of Curcuma longa in managing pain in patients suffering from osteoarthritis. Literature was created through various reference sources such as Pubmed, ScienceDirect, Google Scholar, and Epistemonikos which were screened against several inclusion criteria from 2013 - 2023. From the 277 articles obtained, 2 articles were obtained. Curcuma longa has been proven to significantly reduce pain scores according to VAS and WOMAC criteria. Apart from that, its effectiveness is not much different compared to non-steroidal anti-inflammatory drugs (NSAIDs). However, fewer side effects were reported in the Curcuma longa group. Curcuma longa can be used as a therapeutic option for mild to moderate osteoarthritis, especially in patients who cannot tolerate the side effects of NSAIDs.